The Meaning of Tolerance in Quranic Translation: Addressing the Challenge of Islamophobia in the Western World - Vasco Fronzoni (Qiyam Islamic Studies Center Foundation, 2025)
This article discusses the complexities of translating the Qur’an and the importance of accurately conveying core Islamic principles like Tolerance and Freedom of belief. The research aims to highlight the unique challenges of translating the Qur’an into languages other than Arabic due to its divine nature of the Revelation and linguistic intricacies. It also seeks to correctly define and explain the Islamic principles of Tolerance and Freedom of belief, especially for non-Arabic-speaking and non-Muslim people, emphasizing their relevance for Social inclusion and combating social tensions in European societies. For the methodology, the article examines the theological and linguistic difficulties of Quranic translation, analysing the concept of Tolerance within Islamic tradition, linking it to the Maqāṣid al-Sharīʿa. The study further explores specific Quranic verses and aḥādith to illustrate Islamic teachings on patience, understanding, non-compulsion in faith, and the inherent human right to diverse opinions and peaceful coexistence. Regarding the findings, the article illustrate that translating the Qur’an presents significant challenges, including rhetorical figures and the theological dilemma of altering Divine speech. However, viewing translations as commentaries helps overcome these issues and allow dissemination of Divine teachings. Islam explicitly promotes Tolerance and Freedom of belief, emphasizing patience, understanding, and the acceptance of human diversity. While advocating for “promoting good and preventing evil”, Islam prohibits imposing beliefs through force, useful for dealing with the problems of tension and intolerance, often present in Europe. In the conclusions, the research argue that starting from the principle that the Qur’an clearly states that there is no compulsion in religion, it must be underlined that Islam is fundamentally a Religion of Tolerance and Respect, providing ample space for Freedom of Expression and Belief. Clarifying this concept is essential to overcome the difficulties of Muslim communities living in Europe and Italy, with reference to the critical issues of radicalization, Islamophobia and social inclusion.